Model for End-Stage Liver Disease and Sodium Velocity Predicts Overall Survival in Nonmetastatic Hepatocellular Carcinoma Patients - Justin Y. Tang; Nitin Ohri; Rafi Kabarriti; Santiago Aparo; Jennifer Chuy; Sanjay Goel; Jonathan M. Schwartz; Milan Kinkhabwala; Andreas Kaubisch; Chandan Guha (Canadian Journal of Gastroenterology and Hepatology)
Background & Aims. The significance of short-term changes in model for end-stage liver disease and Sodium (MELD-Na) following hepatocellular carcinoma (HCC) diagnosis is unknown. In this report, we explore the value of the rate of short-term changes in MELD-Na as an independent predictor of mortality in patients with nonmetastatic HCC. Methods. We reviewed a cohort of patients diagnosed with nonmetastatic HCC at our institution between 2001 and 2011. We evaluated potential predictors of overall survival, including baseline MELD-Na and the change in MELD-Na over 90 days. We explored survival times of cohorts grouped by baseline MELD-Na and the change in MELD-Na. Results. 182 patients met eligibility criteria. With a median follow-up of 21 months for surviving patients, 110 deaths were observed (60%). Median MELD-Na at the time of diagnosis was 9.7 (IQR 7.5 to 13.9). The median changes in percentage of MELD-Na over 90 days were an increase of 9% (IQR -4% to 55%). Multivariable Cox proportional hazards modeling demonstrated that both baseline MELD-Na (HR=1.07 per unit increase, 95% CI 1.03 to 1.11, p<0.001) and changes in MELD-Na exceeding 40% (HR=3.69, 95% CI 2.39 to 5.69, p<0.001) were independently associated with increased mortality risk. Median survival among patients whose changes in MELD-Na were greater than 40% was 4.5 months, and median survival among the 131 other patients was 25.8 months (p<0.001). Conclusions. We identified a subset of HCC patients who have extremely poor prognosis by incorporating the rate of short-term change in MELD-Na to baseline MELD-Na score.